Applied reconfigurable computing : architectures, tools, and applications : 14th International Symposium, ARC 2018, Santorini, Greece, May 2-4, 2018, proceedings /: 14th International Symposium, ARC 2018, Santorini, Greece, May 2-4, 2018, proceedings. (2018) - Unknown
No abstract available